Analisis Biaya Transaksi pada Kelembagaan Pertanian Gapoktan Penerima Program Pengembangan Usaha Agribisnis Pedesaan (PUAP) di Desa Raman Aji Kecamatan Raman Utara Kabupaten Lampung Timur - Zulkarnain Zulkarnain; Windu Mangiring (Politeknik Negeri Lampung., 2017)
Gapoktan (Combined Farmer Group) is an agricultural institution implementin PUAP program. In the implementation of the PUAP program, transaction costs can not be avoided. Transaction costs become something that is considered normal and activities become commonplace in the process of making contracts and efforts to achieve common goals.This study aims to analyze and study the structure of transaction costs on agricultural institutions Gapoktan recipient PUAP program in East Lampung regency. The location of this research was conducted in Raman Aji Village, North Raman District, East Lampung Regency.Sampling technique used purposive sampling method (purposely) and simple random sampling method (simple random). Respondents in this study were the chairman and members of farmer group receiving PUAP program at Gapoktan Jaya Makmur in Raman Utara District of East Lampung Regency as many as 68 people.To answer the purpose of research used transaction cost analysis (transaction cost). The result of this research is PUAP program aid fund of Rp. 500.000,00 per member Gapoktan got average transaction cost equal to Rp. 203.235.00. The contract security cost is the largest transaction cost when compared with the information cost and the coordination cost which is 58.61%.